2021
DOI: 10.1186/s12913-020-06031-6
|View full text |Cite
|
Sign up to set email alerts
|

How do inner and outer settings affect implementation of a community-based innovation for older adults with a serious illness: a qualitative study

Abstract: Background Implementing community-based innovations for older adults with serious illness, who are appropriate for a palliative approach to care, requires developing partnerships between health and community. Nav-CARE is an evidence-based innovation wherein trained volunteer navigators advocate, facilitate community connections, coordinate access to resources, and promote active engagement of older adults within their communities. Acknowledging the importance of partnerships between organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…These barriers and facilitators related to public knowledge and perceptions of palliative care; social and financial organizational capital; and skilled leadership. 24 , 28 In the study reported in this article, we were able to analyze those factors across diverse contexts to develop a more nuanced understanding of the factors that must be in place to produce a robust and sustainable program. These four factors were organizational capacity, stable and engaged leadership, a focused client population, and skillful messaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These barriers and facilitators related to public knowledge and perceptions of palliative care; social and financial organizational capital; and skilled leadership. 24 , 28 In the study reported in this article, we were able to analyze those factors across diverse contexts to develop a more nuanced understanding of the factors that must be in place to produce a robust and sustainable program. These four factors were organizational capacity, stable and engaged leadership, a focused client population, and skillful messaging.…”
Section: Discussionmentioning
confidence: 99%
“…health and community systems), the inner organizational setting where Nav-CARE was implemented, the characteristics of the individuals involved in implementing Nav-CARE, and the process of delivering Nav-CARE. 28 The mixed-method data collection strategy was guided by the four research questions:…”
Section: Data Collectionmentioning
confidence: 99%
“…Because the nature of each laboratory session was group based, this same format was selected for the interviews in an effort to maximize involvement while minimizing scheduling challenges and participant burden. This structure also enabled questions to be asked systematically in a direct manner by the interviewer to each participant on an individual level (in contrast with a focus group, where participants interact more with one another) [ 48 - 50 ]. One-on-one interviews were conducted when only 1 participant among those attending the post-app session expressed interest in participating or when a participant wished to participate but had a scheduling conflict with the group-based session.…”
Section: Methodsmentioning
confidence: 99%
“…More frequently, older adult researchers have used CFIR in nursing homes and acute care settings 10,13 . Ongoing efforts to adapt CFIR for frail older adult primary care populations are underway, as is the work to conceptualize inner and outer settings that affect community‐based innovations for those with more severe injury or illness in complex healthcare settings 17–19 …”
Section: Implementation Science Barriers For Geriatrics Researchersmentioning
confidence: 99%